2012
DOI: 10.1111/j.1399-3054.2012.01596.x
|View full text |Cite
|
Sign up to set email alerts
|

Solar UV‐B effects on PSII performance in Betula nana are influenced by PAR level and reduced by EDU: results of a 3‐year experiment in the High Arctic

Abstract: The long-term and diurnal responses of photosystem II (PSII) performance to near-ambient UV-B radiation were investigated in High Arctic Betula nana. We conducted an UV exclusion experiment with five replicated blocks consisting of open control (no filter), photosynthetic active radiation and UV-B transparent filter control (Teflon), UV-B-absorbing filter (Mylar) and UV-AB-absorbing filter (Lexan). Ethylenediurea (EDU), a chemical normally used to protect plants against ozone injury, was sprayed on the leaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 101 publications
1
4
0
Order By: Relevance
“…Therefore, although we cannot identify whether such oxidative burst was generated by the synergic effect of O 3 and drought, or by severe drought alone, our results suggest the capability of EDU to interact with other oxidative stress factors besides O 3 . This supports the results obtained by Middleton et al [68] and Albert et al [37], who demonstrated that, in the absence of O 3 , EDU substantially ameliorated UV-B damage caused to foliage in soybean and birch, thus highlighting the need to better investigate the possible confounding effect of such abiotic stress factors, before using EDU as an O 3 protectant in the field.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, although we cannot identify whether such oxidative burst was generated by the synergic effect of O 3 and drought, or by severe drought alone, our results suggest the capability of EDU to interact with other oxidative stress factors besides O 3 . This supports the results obtained by Middleton et al [68] and Albert et al [37], who demonstrated that, in the absence of O 3 , EDU substantially ameliorated UV-B damage caused to foliage in soybean and birch, thus highlighting the need to better investigate the possible confounding effect of such abiotic stress factors, before using EDU as an O 3 protectant in the field.…”
Section: Discussionsupporting
confidence: 89%
“…In this context, the possible interaction of EDU with other oxidative stress factors besides O 3 should be further investigated. Indeed, Albert et al [37] have shown that EDU application counteracted some of the negative impacts of UV-B on Betula nana L., thus suggesting that EDU can protect plants from other oxidative stress factors besides ozone. Recently, Xin et al [38] showed that moderate drought does not affect the capability of EDU to protect potted Populus plants from O 3 , but, to the best of our knowledge, no study has investigated the possible confounding effect of drought when using EDU under Mediterranean environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…At high latitudes ϕ PSII was shown to increase with winter warming of evergreen sub‐Arctic shrubs in northern Sweden (Bokhorst et al ., ); this result is consistent with our observations of reduced ϕnormalCO2 at low temperature. These, and other studies (Marchand et al ., ; Albert et al ., ) that measured ϕ PSII in Arctic and sub‐Arctic species, have also shown a range of ϕ PSII (0.55–0.75) that is consistent with stressed vegetation, which is in contrast with the higher (0.83) and remarkably consistent ϕ PSII of unstressed leaves (Baker, ). In Arctic shrubs, including S. pulchra , high xanthophyll pigment pools and high de‐epoxidation of those pools support the potential for high xanthophyll cycle activity, and the deployment of photoprotective mechanisms in Arctic species that are consistent with acclimation or adaptation to stress (Magney et al ., ).…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, most TBMs assume the same quantum yield for all PFTs and do not include any temperature sensitivity for this parameter (Dietze, 2014;Rogers et al, 2017). While this assumption is robust for many PFTs and biomes, it does not account for observations of low quantum yield that are associated with the typically cold growth temperatures experienced by arctic and boreal vegetation (Albert et al, 2012;Bokhorst et al, 2010;Kolari et al, 2014;Marchand et al, 2006;Rogers et al, 2019;Solanki et al, 2019;Wallin et al, 2013).…”
Section: Quantum Yield: a Critical Knowledge Gap And A Unique Opportu...mentioning
confidence: 99%
“…Therefore, most TBMs assume the same quantum yield for all PFTs and do not include any temperature sensitivity for this parameter (Dietze, 2014; Rogers et al, 2017). While this assumption is robust for many PFTs and biomes, it does not account for observations of low quantum yield that are associated with the typically cold growth temperatures experienced by arctic and boreal vegetation (Albert et al, 2012; Bokhorst et al, 2010; Kolari et al, 2014; Marchand et al, 2006; Rogers et al, 2019; Solanki et al, 2019; Wallin et al, 2013). Reductions in quantum yield and convexity (which determines the irradiance at which light saturation is reached), and slow recovery from photoprotection and photodamage reduce carbon gain by up to 32% in crop systems, and transgenic tobacco that had been bioengineered for a rapid recovery from photoprotection has a 15% increase in photosynthesis and yield (Kromdijk et al, 2016; Murchie & Ruban, 2020; Zhu et al, 2004).…”
Section: Improving Physiological Parameterization Of High‐latitude Pf...mentioning
confidence: 99%